Identification of the Prognosis-Related lncRNAs and Genes in Gastric Cancer - Su, Xiaohui; Zhang, Jianjun; Yang, Wei; Liu, Yanqing; Liu, Yang; Shan, Zexing; Wang, Wentao (Frontiers in Genetics, 2020)
Gastric cancer is a common malignant tumor with high occurrence, recurrence and the leading cause of death worldwide. However, the prognostic value of the protein-coding and non-coding RNAs in stage III gastric cancer has not been systematically analyzed. In this study, we identified 585 long noncoding RNAs (lncRNAs) and 927 protein-coding genes (PCGs) correlated with the overall survival of gastric cancer. The functional enrichment analysis revealed that the prognostic genes positively correlated with death rates were enriched in the pathways including gap junction, focal adhesion, cell adhesion molecules (CAMs), and neuroactive ligand-receptor interaction were involved in the tumor microenvironments and cell-cell communications, suggesting that their dysregulation may promote the tumor progression. To evaluate the performance of the prognostic genes in the risk prediction, we built three Cox models based on prognostic genes. The performance of the three models based on features from only PCGs, lncRNAs, and all prognostic genes were systematically compared, which revealed that the features selected from all the prognostic genes showed higher performance than the features selected only from lncRNAs or PCGs. Furthermore, the multivariable Cox regression analysis revealed that the stratification with the highest performance had was an independent prognostic factor in stage III gastric cancer. In addition, we explored the underlying mechanism of the prognostic lncRNAs in the Cox model by predicting the lncRNA and protein interaction. Specifically, CTD-2218G20.2, was predicted to interact with PSG4, PSG5, and PSG7, which could also interact with cancer-related proteins, including KISS1, TIMP2, MMP11, IGFBP1, EGFR, and CDKN1C, suggesting that CTD-2218G20.2 might participate in the cancer progression via these cancer-related proteins. In summary, the systematic analysis of the prognostic lncRNAs and PCGs was of great importance to the understanding of the progression of stage III gastric cancer.